Exploring Kimberley bushfires in space and time - Turdukulov, Ulanbek; Fazio, T. (2016)
The occurrence and spread of bushfires is a complex interplay of several environmental and social factors. There have been a number of studies that allow bushfire modelling and simulations prior to or during fire events. However, none of these systems is able to look beyond the initial phase of a bushfire event and provide a historical overview of bushfire developments: their occurrences and lifetimes, movement behaviours and size variations and general patterns over space and time. This overview is important for observing trends in bushfires as well as for calibrating the model parameters. The aim of this project is to perform such a spatio-temporal overview of bushfires in the Kimberleyregion of Western Australia. The source data are daily fire hotspots over the last decade from 2004 until 2014 obtained from Landgate. These hotspots are used to identify individual fires and track their movements in time. Then using descriptive statistics and two visualization methods such as animationand space-time cube, spatio-temporal patterns and trends are explored. It was found that on average bushfires had a lifetime of three days and there was a rising trend for bushfires recorded over the ten years, with most fires occurring near the coastal areas of the region in 2012. At the peak of the trend, there was also an emergence of much larger fires occurring in the southeast inland regions. Several environmental and social factors can correlate with the increase in size and frequency of the fires overthe last few years that require further investigation.